The labour market in CGE models - Stefan Boeters; Luc Savard (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This chapter reviews options of labour market modelling in a CGE framework. On the labour supply side, two principal modelling options are distinguished and discussed: aggregated, representative households and microsimulation based on individual household data. On the labour demand side, we focus on the substitution possibilities between different types of labour in production. With respect to labour market coordination, we discuss several wage-forming mechanisms and involuntary unemployment.
Keywords: C68; D58; J20; J64; 330; computable general equilibrium model; labour market; labour supply; labour demand; microsimulation; involuntary unemployment; Arbeitsmarkttheorie; Arbeitslosigkeit; Arbeitsnachfrage; Arbeitsangebot; Allgemeines Gleichgewicht; Simulation; Theorie